China-CEE Relations in a New Era: The Drivers behind the Development of the Platform for Regional Cooperation 16+1. (2022)
Relations between China and the countries in Central and Eastern Europe (CEE) experienced a rapid and profound deepening from 2009 to 2019, with the 16+1 regional platform for cooperation playing a central role. From the Chinese side, what are the motivations behind the establishment of 16+1? Through a literature review, the article identifies three sets of drivers: pragmatic, political, and historical. The increasing priority given by China to relations with the European Union is also leading to a shift in how the country understands and interacts with CEE, resulting in the Europeanization of 16+1.